Effect of Precision Feeding SID Lysine and Amino Acids to Lactating Sows Compared to a Conventional Feeding Strategy on Sow and Litter Performance and Feed Cost in a Commercial Farm - Mikayla S. Spinler; Jordan T. Gebhardt; Joel M. DeRouchey; Mike D. Tokach; Robert D. Goodband; Hyatt L. Frobose; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 728 gilts and parity 1 sows (Camborough, PIC, Hendersonville, TN) and litters (Camborough × PIC 800) were used in a 19-day lactation study to evaluate the effects of precision feeding Lys and other amino acids compared to providing a single lactation diet at a commercial sow farm. Sows were blocked by parity and allotted to one of two treatments at entry into the farrowing rooms. Treatments consisted of a single 1.07% SID Lys lactation diet or a blend of a high and low SID Lys diet to provide a specific targeted SID Lys intake for each day of lactation. Two diets were used to create the blended dietary treatment, a low Lys diet (0.60% SID Lys) or a high Lys diet (1.07% SID Lys). Sows fed the control diet treatment were fed only the high Lys diet. Sows on the blended diet treatment were fed a blend of the low and high Lys diet to target a specific Lys intake for each day of lactation using the Gestal Quattro Opti feeder (Jyga Technologies, St-Lambert-de-Lauzon, Quebec, Canada). Lysine intake targets were based on the NRC (2012) model estimates for gilts and sows with 17 piglets, with the exception that levels were increased by 20% to reach a targeted average Lys intake of approximately 63 g/d. Average Lys intake was 87% of target because sow feed intake during lactation was lower than predicted. As expected, sows fed the control diet treatment had greater (P < 0.001; 72.0 vs. 54.8 g/d) Lys intake compared to sows fed the blended diet treatment because they were fed only the high Lys diet. No differences (P > 0.05) in entry-to-wean change in sow BW, backfat or loin depth, caliper score, or ADFI were observed between treatments. There were no differences (P > 0.05) in litter size at d 2 after equalization or weaning between treatments; however, litters and piglets from sows fed the control treatment tended to have a greater weaning weight (P = 0.075) and ADG (P = 0.090) compared to litters and piglets from sows fed the blended diet treatment. This is likely due to low Lys intake for sows fed the blend diet treatment to maximize litter growth performance. Feed cost per sow was lower (P < 0.05) for sows fed the blend curve in both a low and high ingredient price scenario. No differences (P > 0.05) in feed cost per lb of litter weight gain were observed; however, feed cost per weaned pig was lower (P < 0.05) for sows fed the blended diet treatment. Sows fed the control diet treatment had a higher (P < 0.05) serum urea nitrogen concentration on d 10 and at weaning compared to sows fed the blended diet treatment. Differences were also observed for milk crude protein content on d 10 and at weaning, with sows fed the control diet treatment having greater crude protein (P = 0.05) compared to sows fed the blended diet, also likely contributing to the differences observed in piglet weaning weight. Precision feeding sows using diet blending during lactation can be used to reduce feed cost, but future research should focus on using technology to automatically adjust diet blends for low or high feed intake sows to avoid the under or overfeeding of nutrients.
Keywords: Lactation; lysine; precision feeding